2005
DOI: 10.3390/i6010130
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Sulfur Dioxide on Carbons Catalyzed by Salts

Abstract: Abstract. The reduction of SO2 on different carbons in the presence of the nitrates and sulfides of sodium, potassium and calcium and potassium polysulfides was studied. The presence of salts increased the initial rate 2-5 fold for all of them and did not change the product distribution. The catalysis was not determined by the cation and there was no difference in the catalytic reactivity between nitrates and sulfides. The sulfur content of the activated carbon increased during the reaction on account of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…This suggests that the sulfur promotes the graphitization of the carbon matrix despite the fact that air activation usually induces defects. The mechanism for this phenomenon may be explained by sulfur atoms in gaseous SO/SO 2 preferably adsorbing on the defective sites of carbon and reacting with nearby imperfectly located carbon atoms [47][48][49]. In other words, the greater the amount of sulfur oxides gaseous released (sulfur oxides are derived from sulfur on the surface), the higher the degree of graphitization of the carbon.…”
Section: Degree Of Graphitizationmentioning
confidence: 96%
“…This suggests that the sulfur promotes the graphitization of the carbon matrix despite the fact that air activation usually induces defects. The mechanism for this phenomenon may be explained by sulfur atoms in gaseous SO/SO 2 preferably adsorbing on the defective sites of carbon and reacting with nearby imperfectly located carbon atoms [47][48][49]. In other words, the greater the amount of sulfur oxides gaseous released (sulfur oxides are derived from sulfur on the surface), the higher the degree of graphitization of the carbon.…”
Section: Degree Of Graphitizationmentioning
confidence: 96%
“…[2] Sulfur transport out of the matrix proceeds through consecutive reactions of sulfur insertion generating intermediates that release sulfur as S 2 . [6] Sulfur dioxide can also be selectively incorporated in the matrix of MPGO as oxidized intermediates, at ambient temperature, via excitation by non-thermal plasma. [4] The calculated X-ray photoelectron spectrum (XPS) composition, using the atom inventory technique, [7] suggested that the insertion occurred along with partial reduction of MPGO and CO 2 generation.…”
Section: Introductionmentioning
confidence: 99%
“…We proposed the mechanism of sulfur transport shown in Figure (adapted to the TBA model) where, after the extrusion of atomic sulfur from the benzothiirene site 3 , the sulfur reacts with another benzothiirene site through a thiosulfoxide intermediate to generate a disulfane which eliminates diatomic sulfur and the original unsaturated bond, or consecutively, accepts a third atom and form a trisulfane able to extrude S 2 regenerating the benzothiirene site. Formation of a trisulfane from the disulfane or from the benzothiirene site allows the extrusion of a more stable form of sulfur, a singlet diatomic sulfur 1 S 2 , that would regenerate the benzothiirene site, establishing an equilibrium sulfane-disulfane-trisulfane that would function as a cycle of capture–release of sulfur.…”
Section: Resultsmentioning
confidence: 99%
“…Episulfide 3 initiates the transport of sulfur out the carbon matrix. 52 The mechanism of CO 2 formation has not been studied yet and will be discussed in this work. For this reason, the fragment of the residual carbon matrix in Figure 1 is not described.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation